Experimental investigation on rock breaking performance of cutter assisted with hydraulic fracturing. (1st May 2021) - Li, Hongsheng; Liu, Songyong; Zhu, Zhencai; Liu, Hao; Zhang, Deyi; Guo, Chuwen
Highlights: Cracks propagation is affected by the position and number of empty holes. Circumferential distribution holes have important effects on hydraulic fracture. Rock breaking performance of cutter assisted with hydraulic fracturing is better. Rock cutting by cutter assisted with hydraulic fracturing provides a possibility for fast excavation. Abstract: To improve the efficiency of cutting hard rocks in roadway tunneling, a rock breaking method using a cutter assisted with hydraulic fracturing is proposed. In addition, the influence of the circumferential distribution of holes on the crack propagation was studied through a hydraulic fracturing experiment. On this basis, an experiment of rock breaking by a cutter assisted with hydraulic fracturing was conducted, and the effect of the hydraulic fracturing on the cutting performance was analyzed. The results show that the main cracks' initial direction and propagation path were influenced by the location and number of circumferentially distributed holes, around which the secondary cracks appeared. During the fracturing process, the main cracks expanded to the circumferentially distributed holes and developed into a crack network; the more empty holes there were, the denser the crack network was. Compared with the original rock samples, the cutting torque and propelling force of the non-directionally and directionally perforated fractured rock samples were significantly lower, and the cutting performance of the directionally perforated fractured rock samples was better. The research provides a possibility for the rapid excavation of extremely hard and abrasive rock.